Evaluation and suggestions for improvement of seismic design procedures for R - Kappos, Andreas J. (Earthquake engineering & structural dynamics.)
This paper aims to shed some further light on the seismic behaviour and design of reinforced concrete (R/C) walls which form part of dual (frame + wall) structures. The significance of post-elastic dynamic effects is recognized by most seismic codes in the definition of the design action effects on walls, i.e. bending moments and shear forces. However, the resulting envelopes are not always fully satisfactory, particularly in the case of medium-to-high-rise buildings. The relevant provisions of modern seismic codes are first summarized and their limitations discussed. Then an extensive parametric study is presented which involves typical multi-storey dual systems that include walls with unequal lengths, designed according to the provisions of Eurocode 8 for two different ductility classes (M and H) and two effective peak ground acceleration levels (0.16 and 0.24g). The walls of these structures are also designed according to other methods, such as those used in New Zealand and Greece. The resulting different designs are then assessed by subjecting the structures to a suite of records from strong ground motions, carrying out inelastic time history analysis, and comparing the results with the design action effects. It is found that for (at least) the design earthquake intensity, the first two modes of vibration suffice for describing the seismic response of the walls. The bending moment envelope, as well as the base shear of each wall, is found to be strongly dependent on the second mode effect. As far as the code-prescribed design action effects are concerned, only the NZ Code was found to be consistently conservative, whereas this was not always the case with EC8. A new method is then proposed which focuses on quantifying in a simple way the second mode effects in the inelastic response of the walls. This procedure seems to work better than the others evaluated herein.